Do Low-Dose Oral Contraceptives have an Effect on Ovarian Endometrioma Diameter and Endometriosis Symptoms?. Issue 4 (October 2013) - Del Forno, Simona; Solfrini, Serena; Ferrini, Giulia; Zannoni, Letizia; Bertoldo, Valentina; Monti, Giorgia; Leonardi, Deborah; Labate, Antonio Maria Morselli; Paccapelo, Alexandro; Seracchioli, Renato
Purpose: To investigate the effect of a low-dose oral contraceptive containing drospirenone/ethinylestradiol 3 mg/20 μg on endometrioma mean diameter. Methods: Fifty women with sonographic diagnosis of ovarian endometrioma and at least 12 months of therapy with drospirenone/ethinylestradiol 3 mg/20 μg, without previous adnexal surgery, were selected for this retrospective study. Endometrioma mean diameter measured with transvaginal ultrasonography and endometriosis-associated symptoms evaluated by a visual analogue scale (VAS) score (0-10) were reported at therapy prescription (baseline) and after 6, 12 and 18 months of treatment. Main outcome measures were endometrioma mean diameters and endometriosis-associated symptoms variations during the follow-up; differences between cyclic and continuous regimen were also considered. Results: A significant reduction in endometrioma mean diameter was observed during the follow-up. The reductions of mean diameter versus baseline values were significantly higher in continuous users than in cyclic users at 6 and 18 months of follow-up. No new endometriomas occurred. The dysmenorrhea VAS score significantly decreased during the follow-up. Conclusions: Drospirenone/ethinylestradiol 3 mg/20 μg seems to be effective in reducing endometrioma mean diameter. The continuous regimen seems to be associated with a greater reduction than the cyclic one.